Strategi Guru dalam Meningkatkan Pemahaman Konsep Kalimat Efektif Menggunakan Model Contextual Teaching and Learning pada Siswa Sekolah Dasar - Chindy Putri A1; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine teachers' strategies in improving students' understanding of effective sentence concepts through the implementation of the Contextual Teaching and Learning (CTL) model in elementary schools. The issues addressed in this research include how teachers design and implement context-based learning strategies, the challenges encountered during implementation, and the impact on students’ understanding of effective sentence structures. This research employs a literature review method by analyzing various journals, scholarly articles, and relevant documents. The findings indicate that teaching strategies that connect instructional materials with students’ real-life contexts—through CTL components such as constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment—are proven to significantly enhance students’ understanding of effective sentences. Furthermore, the implementation of interactive and meaningful strategies also increases student participation and fosters positive attitudes toward learning the Indonesian language. However, the application of CTL faces several challenges, including limited instructional time, teacher readiness, and diverse student abilities. Therefore, support from the school and professional development for teachers is essential to ensure that CTL-based teaching strategies can be implemented optimally and sustainably.